2009
DOI: 10.1007/s11783-009-0013-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the photodegradation of N-nitrosodimethylamine in drinking water

Abstract: In order to provide basic data for practical application, photodegradation experiment of Nnitrosodimethylamine (NDMA) in aqueous solution was carried out with a low-pressure Hg lamp. Effects of the initial concentration of NDMA, solution pH, dissolved oxygen, and the presence of humic acid on NDMA photodegradation were investigated. NDMA at various initial concentrations selected in this study was almost completely photodegraded by UV irradiation within 20 min, except that at 1.07 mmol/L, NDMA could be photode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…During the photolysis of RNTD and NZTD, the NO 2 À concentration was always higher than NO 3 À concentration. Xu et al (2009) observed similar results at neutral pH also, i.e., the concentration of NO 3 À produced was much lower than that of NO 2 À during the photolysis of nitroso-containing compounds. The formation of NO 3 À may be derived from the oxidation of NO 2 À .…”
Section: Effect Of Uv Photolysis On Hnmsfpsupporting
confidence: 70%
“…During the photolysis of RNTD and NZTD, the NO 2 À concentration was always higher than NO 3 À concentration. Xu et al (2009) observed similar results at neutral pH also, i.e., the concentration of NO 3 À produced was much lower than that of NO 2 À during the photolysis of nitroso-containing compounds. The formation of NO 3 À may be derived from the oxidation of NO 2 À .…”
Section: Effect Of Uv Photolysis On Hnmsfpsupporting
confidence: 70%
“…However, the absorption is also pH-dependent [118,119]. Therefore, one might expect photolytic destruction to also depend on the solution's pH.…”
Section: Photolytic Reactions and Advanced Oxidation Processesmentioning
confidence: 99%
“…Therefore, one might expect photolytic destruction to also depend on the solution's pH. Indeed, Xu et al [118,120] have shown that an acidic pH favors the destruction of nitrosamine, while an alkali pH may substantially retard the process. The earlier work of Stefan and Bolton [121] indicated also that the photolytic destruction of NDMA is favored by acidic conditions.…”
Section: Photolytic Reactions and Advanced Oxidation Processesmentioning
confidence: 99%
“…Nitrate and nitrite have been reported in literature to be formed under NDMA photodegradation in weakly acidic water solution (Plumlee and Reinhard, 2007). However literature findings also suggest that in alkaline solutions, other inorganic nitrogen products than nitrate and nitrite like N 2 and N 2 O are formed (Xu et al, 2009a;Stefan and Bolton, 2002).…”
Section: Uv-light Tests With 50 Wt% Deamentioning
confidence: 98%